1995
DOI: 10.1136/oem.52.7.464
|View full text |Cite
|
Sign up to set email alerts
|

Lorry drivers' work stress evaluated by catecholamines excreted in urine.

Abstract: Objectives-To evaluate lorry drivers' work stress by measurement of adrenaline and noradrenaline excreted in the urine, and to find out which factors in their working situation are related to the excretion rates of these catecholamines. Methods-The urinary excretion of adrenaline and noradrenaline of 32 lorry drivers, who also had loading and unloading activities to perform, was studied for one working day and one rest day. Each driver was asked to provide six urine samples on both days. Results-For all sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 17 publications
(3 reference statements)
2
32
1
2
Order By: Relevance
“…Correlation coefficients between job stress index and heart rate variability, urinary catecholamine and duration of employment Table 4. Mean (± standard deviation) of log transfer low-frequency power of heart rate variability (LF power), HFnu, LFnu, LF/HF, age, smoking status and alcohol consumption for job stress group stratified by duration of employment norepinephrine, during the workday were higher than those found in earlier studies of professional drivers, and the recovery period after the completion of daily work was relatively insufficient 11) . A recent biomarker study of 106 Japanese hospital workers with greater psychological job stress reported lower brain-derived neurotrophic factor levels and higher plasma 3-methoxy-4-hydroxyphenylglycol levels than in workers suffering from less job stress 23) .…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…Correlation coefficients between job stress index and heart rate variability, urinary catecholamine and duration of employment Table 4. Mean (± standard deviation) of log transfer low-frequency power of heart rate variability (LF power), HFnu, LFnu, LF/HF, age, smoking status and alcohol consumption for job stress group stratified by duration of employment norepinephrine, during the workday were higher than those found in earlier studies of professional drivers, and the recovery period after the completion of daily work was relatively insufficient 11) . A recent biomarker study of 106 Japanese hospital workers with greater psychological job stress reported lower brain-derived neurotrophic factor levels and higher plasma 3-methoxy-4-hydroxyphenylglycol levels than in workers suffering from less job stress 23) .…”
Section: Discussioncontrasting
confidence: 44%
“…Occupationally-induced reactivity in the levels of urinary catecholamines have been documented in bus drivers 12) and truck drivers 11) . In the latter study, excretion rates of epinephrine, and especially Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other field studies (4, [15][16][17][18][19][20][21], the measurement of catecholamines took place via urine for an overall view of the reactivity over large time periods. Cortisol has been measured more often in saliva (22)(23)(24)(25)(26)(27)(28).…”
Section: Catecholamines and Cortisolmentioning
confidence: 99%